A meta-analysis of the value of indocyanine green fluorescence imaging in guiding surgical resection of primary and metastatic liver cancer - Dali Xiong; Jiaran Li; Li Li; Fuhao Xu; Tao Hu; He Zhu; Xiaohui Xu; Yawen Sun; Shuanghu Yuan (Photodiagnosis and Photodynamic Therapy)
Objective: This meta-analysis aimed to evaluate the value of indocyanine green fluorescence imaging in precision resection surgery for primary and metastatic liver cancer. Methods: A systematic search of PubMed, Embase, Scopus, Cochrane Library, Web of Science, ScienceDirect, and major scientific websites was conducted until June 2024. Randomized controlled trials and observational studies comparing indocyanine green fluorescence imaging-guided liver cancer resection with traditional methods were included. The meta-analysis incorporated overall outcomes and subgroup outcomes based on liver cancer types (primary and metastatic). StataSE 12.0 software was used for statistical analysis after a quality assessment of the included studies. Results: Twenty studies involving 1,283 patients with liver cancer were included. The results showed that indocyanine green fluorescence imaging significantly reduced intraoperative blood loss [Weighted mean difference (WMD), –88.75; 95 % CI, –128.48 to –49.02, p < 0.05], transfusion rate [Odds ratios (OR), 0.5; 95 % CI, 0.36–0.7, p < 0.05], hospital stay duration [WMD, –1.11; 95 % CI, –1.79 to –0.43, p < 0.05], and the overall complication rate [OR, 0.59; 95 % CI, 0.44–0.79, p < 0.05]. However, no significant differences were observed in operative time or in the subgroup analysis for metastatic liver cancer. Conclusion: Indocyanine green fluorescence imaging is a safe and effective intraoperative navigation technique that improves surgical outcomes and prognostic indicators in liver cancer resection. However, its efficacy in metastatic liver cancer surgery requires further validation through larger-scale, rigorous, prospective, randomized controlled trials.